Alternative Viewpoint Against Breast Cancer Based on Selective Serotonin Receptors 5HTR3A and 5HTR2A Antagonists that can Mediate Apoptosis in MCF-7 Cell Line - Hejazi, Seyed H.; Ahangari, Ghasem; Deezagi, Abdolkhaegh (Current Drug Discovery Technologies, 2015)
Background: Neurotransmitters had progressive effects on various cancers via their different type of receptors. Objective: This study was conducted to determine the pattern of serotonin receptors, respectively, 5HTR2A and 5HTR3A gene expression in MCF-7 cells and evaluate their selective antagonist effects on them. Method: RT-PCR was performed to determine the pattern of serotonin receptor gene expression in human breast cancer cell line (MCF-7). MCF-7 cells were cultured and treated via different doses of tropisetron (5HTR3A antagonist) and ketanserin (5HTR2A antagonist) for 48 hours. Oxidative and reductive enzyme activity was carried out by MTT assay. Subsequently, nuclear morphology of cells was observed by mixed dye florescent staining. To validate cell proliferation inhibition, Real time PCR was carried out for determining the descending rate of proliferating cell nuclear antigen (PCNA) gene expression in treating MCF-7 cells. Assessment of quantification of apoptosis and its discrimination with necrosis at single cell level using Flowcytometry technique was performed. Results: Results showed that 5HTR2A and 5HTR3A have expression in MCF-7 cells. Based on our finding, tropisetron and ketanserin had suppression effects on MCF-7 cells proliferation. (93.35% in tropisetron 50 µmoll-1 and 72.36% in Ketanserin 25µmoll-1 concentration). Conclusion: Therefore, the use of tropisetron and ketanserin as an antagonist of serotonin receptor may be as new approaches are recommended for the treatment of breast cancer cells.
Keywords: MCF7